2017
DOI: 10.1093/nar/gkx464
|View full text |Cite
|
Sign up to set email alerts
|

Nascent RNA sequencing reveals mechanisms of gene regulation in the human malaria parasite Plasmodium falciparum

Abstract: Gene expression in Plasmodium falciparum is tightly regulated to ensure successful propagation of the parasite throughout its complex life cycle. The earliest transcriptomics studies in P. falciparum suggested a cascade of transcriptional activity over the course of the 48-hour intraerythrocytic developmental cycle (IDC); however, the just-in-time transcriptional model has recently been challenged by findings that show the importance of post-transcriptional regulation. To further explore the role of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
91
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 84 publications
(107 reference statements)
10
91
2
Order By: Relevance
“…For example, run-on in association with RNA-seq, called global run-on sequencing assay (GRO-seq) in other organisms (21,69,70), would allow the purification of nascent RNA and further sequencing to map and identify the genomic regions that are being transcribed. Additionally, the methodology can be analyzed using a highcontent image system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, run-on in association with RNA-seq, called global run-on sequencing assay (GRO-seq) in other organisms (21,69,70), would allow the purification of nascent RNA and further sequencing to map and identify the genomic regions that are being transcribed. Additionally, the methodology can be analyzed using a highcontent image system.…”
Section: Discussionmentioning
confidence: 99%
“…Other methodologies can be applied, as deep sequencing RNA (RNAseq) and in vitro transcription with radiolabeled nucleotide (20). Differently, in vitro transcription assay allows to quantify the transcriptional activity through the measurement of nascent RNA, that represents a fraction of the total RNA (21). Differently, in vitro transcription assay allows to quantify the transcriptional activity through the measurement of nascent RNA, that represents a fraction of the total RNA (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Lu et al. ). Previous studies revealed that P. falciparum had a very unique mRNA metabolism reflected by the prolonged mRNA decay with the parasite development inside the erythrocytes (Shock et al.…”
mentioning
confidence: 99%
“…Of the five species of malaria parasites that infect humans, Plasmodium falciparum is the most prevalent pathogen and responsible for most deaths (Murray et al 2012, WHO 2014. RNA profilling analysis suggests that there may be an exosome-like complex for RNA metabolism for P. falciparum to achieve its complicated life cycle (Sim et al 2009, Hughes et al 2010Zhang et al 2014a,b;Clayton and Estevez 2011;Bunnik et al 2016, Lu et al 2017. Previous studies revealed that P. falciparum had a very unique mRNA metabolism reflected by the prolonged mRNA decay with the parasite development inside the erythrocytes (Shock et al 2007).…”
mentioning
confidence: 99%